Silybin Alleviated Hepatic Injury by Regulating Redox Balance, Inflammatory Response, and Mitochondrial Function in Weaned Piglets under Paraquat-Induced Oxidative Stress - Long Cai; Dongxu Ming; Wenning Chen; Ying Zhao; Yanpin Li; Wenjuan Sun; Yu Pi; Xianren Jiang; Xilong Li (MDPI AG, 2024)
Silybin (Si) is the main element of silymarin isolated from the seeds of Silybum marianum L. Gaernt., which has superior antioxidant properties. However, the protective role of Si in maintaining liver health under oxidative stress remains ambiguous. This study aimed to investigate the underlying mechanism of the beneficial effect of dietary Si against hepatic oxidative injury induced by paraquat (PQ) in weaned piglets. A total of 24 piglets were randomly allocated to four treatments with six replicates per treatment and 1 piglet per replicate: the control group; Si group; PQ group; and Si + PQ group. Piglets in the control group and PQ group were given a basal diet, while piglets in the Si and Si + PQ groups were given a Si-supplemented diet. On the 18th day, the pigs in the PQ treatment group received an intraperitoneal injection of PQ, and the others were intraperitoneally injected with the same volume of saline. All piglets were sacrificed on day 21 for plasma and liver sample collection. The results showed that dietary Si supplementation mitigated PQ-induced liver damage, as proven by the reduction in liver pathological changes and plasma activity of alanine transaminase and aspartate transaminase. Si also improved superoxide dismutase and glutathione peroxidase activities and total antioxidant capacity, as well as decreased malondialdehyde and hydrogen peroxide concentration in the liver, which were closely related to the activation of the nuclear factor-erythroid 2-related factor 2 signaling pathway. Meanwhile, Si reduced tumor necrosis factor-α and interleukin-8 production and their transcript levels as well as abrogated the overactivation of nuclear factor-κB induced by PQ. Importantly, Si improved mitochondrial function by maintaining mitochondrial energetics and mitochondrial dynamics, which was indicated by the elevated activity of mitochondrial complexes I and V and adenosine triphosphate content, decreased expression of dynamin 1 protein, and increased expression of mitofusin 2 protein. Moreover, Si inhibited excessive hepatic apoptosis by regulating the B-cell lymphoma-2 (Bcl-2)/Bcl-2-associated-X-protein signaling pathway. Taken together, these results indicated that Si potentially mitigated PQ-induced hepatic oxidative insults by improving antioxidant capacity and mitochondrial function and inhibiting inflammation and cell apoptosis in weaned piglets.